Pengaruh Hukum Internasional terhadap Perkembangan Hukum Nasional - Rosmawati Rosmawati (Universitas Syiah Kuala, 2013)
ABSTRACT: This research aims to (1) the process of negotiation as an important process in the alteration of domestic law in terms of determining whether the international conventions should be adopted or not by the government (2) after the ratification, it requires the harmonisation and sincronization institutionally hence it is admitted as the domestic law based on the constitution 1945. (3) all the process heading to the ratification of the convention reflects national politic in increasing international relatinship. Based on those considerations the process must be planned seriously, consistently and continuously by the related institutions under the ministry of foreign affair, and should be consultated with the House of Representative of the Republic of Indonesia. (4) the ratified conventions based on exixting act in the nation must be binding as the rule. The Influence of International Law on the Development of National Law